Quantitative EEG in the neonatal intensive care unit: Current application and future promise - Jennifer C. Keene; Giulia M. Benedetti; Stuart R. Tomko; Réjean M. Guerriero (Annals of the Child Neurology Society)
Abstract Importance Quantitative electroencephalography (qEEG) has been used in the neonatal intensive care unit (NICU) for several decades. Recent innovations have led to renewed interest in expanding its role in the NICU with the goal of improving both acute care of neonates in the NICU and longer‐term outcomes. Observations EEG in the NICU is primarily used to identify neonatal seizures. Sophisticated analysis of EEG can detect other acute neurological emergencies and provide additional information about short‐ and long‐term neurodevelopmental and epileptic prognosis. Using EEG for these additional findings may be limited by access to EEG resources and a constrained supply of neonatal neurophysiologists who can consistently evaluate unique neonatal EEG patterns. Relevance Quantitative EEG analysis is a rapidly developing technology with the potential to augment and support the interpretation of neonatal EEGs. This review focuses on the status of qEEG use in the NICU for identification and prediction of seizures and use in neuroprognostication. It also examines areas of promise for bedside qEEG applications.